Policy and Strategy of Madrasah Heads in Implementing Merdeka Curriculum in MIN 3 Sukoharjo - Praptiningsih Praptiningsih; Daliman Daliman; Nurul Aulia Lilatul Udl-Hiyah; Nike Ardiyani (Universitas Muhammadiyah Enrekang, 2024)
The purpose of this research is to understand the policies and strategies of the madrasah head in the implementation of the Merdeka Curriculum. This research uses a qualitative approach with data collection techniques including observation, documentation, interviews, and data analysis using source triangulation. To test data validity, the researcher uses a credibility test. The results of this research show that the policy of the madrasah head in response to the Ministry of Education's decision regarding the implementation of the Merdeka Curriculum at MIN 3 Sukoharjo involves two stages. First, the madrasah still uses the 2013 curriculum while applying several principles of the Merdeka Curriculum. Second, the madrasah fully implements the Merdeka Curriculum. The strategies used in the implementation of the Merdeka Curriculum include self-learning, attending a series of webinars, and learning through communities